MODERN DIGITALIZATION: PRIORITIES AND PROSPECTS IN THE CONTEXT OF ECONOMIC TRANSFORMATION - Kurpayanidi, Konstantin (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
Advanced technological trends, such as artificial intelligence, robotics, blockchain, virtual and augmented reality technologies, have become the most important catalyst for a new stage of digital transformation. They provided unique opportunities for solving various tasks. Based on the analysis of current trends in the digital economy, the author defines "Digital transformation". The objectives of the presented research are to analyze the current state and prospects for the development of digital technologies and the process of digitalization of the world economy.